The Law and Economics of Best Execution - Macey, Jonathan R.; O'Hara, Maureen (Journal of Financial Intermediation, 1997)
This paper reviews and analyzes the legal and economic aspects of the duty of best execution. Although a well-established principle of securities trading, we show that the dual problems of definition and enforcement make best execution both unwieldy and unworkable as a mandated legal duty. We examine the impact of several market practices on best execution, in particular payment for order flow, preferencing and internalization practices, and price improvement and order execution protocols. We suggest three possible directions for the future rule and interpretation of the duty of best execution.Journal of Economic LiteratureClassification Numbers: G10, G18, K22, K23.